2001
DOI: 10.1023/a:1011974630828
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Trigonella foenum graecum (fenugreek) seed powder has been suggested to have potential antidiabetic effects. The effect of oral administration of Trigonella whole seed powder (5% in the diet) for 21 days on glycolytic, gluconeogenic and NADP-linked lipogenic enzymes were studied in liver and kidney tissues of alloxan-induced diabetic Wistar rats. Diabetic rats were characterised by a 4-fold higher blood glucose level and a 0.7-fold lower body weight compared to normal controls. The activities of the glycolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(32 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Indeed, supplementation of fenugreek seeds in the diets of diabetic rats reduced the hepatic and renal output of glucose by decreasing the levels of the two enzymes glucose-6-phosphatase and fructose-1-6 bisphosphatase in these organs [47]. Other studies have demonstrated that oral administration of fenugreek seed powder to alloxan-diabetic rats could improve glucose homeostasis by normalizing the different glycolytic, lipogenic and related enzyme changes in the liver and kidney [48]. Trigonella seed supplementation in the diet was also reported to partly prevent an increase in the renal glycogen content and a decrease in hepatic glycogen content with diabetes [36].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, supplementation of fenugreek seeds in the diets of diabetic rats reduced the hepatic and renal output of glucose by decreasing the levels of the two enzymes glucose-6-phosphatase and fructose-1-6 bisphosphatase in these organs [47]. Other studies have demonstrated that oral administration of fenugreek seed powder to alloxan-diabetic rats could improve glucose homeostasis by normalizing the different glycolytic, lipogenic and related enzyme changes in the liver and kidney [48]. Trigonella seed supplementation in the diet was also reported to partly prevent an increase in the renal glycogen content and a decrease in hepatic glycogen content with diabetes [36].…”
Section: Discussionmentioning
confidence: 99%
“…Today, fenugreek capsules are freely available, mainly as an appetite stimulant, but immunostimulatory, antidiabetic, antihypertensive and cholesterol-lowering properties have been put forward [2-4,28]. In view of the widespread use of fenugreek and the lack of medical monitoring, the safety of fenugreek seeds consumption during pregnancy turns out to be a public health concern.…”
Section: Discussionmentioning
confidence: 99%
“…Fenugreek seeds are commonly used worldwide for its laxative and galactagogue properties but also to stimulate appetite and prevent stomach ache [1]. More recently, immunostimulatory, antidiabetic, antihypertensive and cholesterol-lowering potentials have been described [2-4]. However, consumption of fenugreek seeds during pregnancy has been associated with congenital malformations, neonatal and birth defects [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, loss of body weight was suppressed by HemoHIM. Failure of STZ-induced diabetic animal models to gain body weight has already been reported [29, 30]. Kidney and liver weights are higher in diabetic animals, as STZ-induced diabetic animals undergo glomerular hypertrophy [31] and triglyceride accumulation [30] in the kidney and liver, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Failure of STZ-induced diabetic animal models to gain body weight has already been reported [29, 30]. Kidney and liver weights are higher in diabetic animals, as STZ-induced diabetic animals undergo glomerular hypertrophy [31] and triglyceride accumulation [30] in the kidney and liver, respectively. In the current study, HemoHIM attenuated hypertrophy of organs (kidney, liver, and lung) and the thymus in STZ-induced diabetic mice [32, 33].…”
Section: Discussionmentioning
confidence: 99%